2016
DOI: 10.1002/2016gl070346
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamics of paleo‐Pacific plate subduction constrained by the source lithologies of Late Mesozoic basalts in southeastern China

Abstract: Widespread Late Mesozoic volcanic magmatism in southeastern China is generally thought to represent products in response to the subduction of paleo‐Pacific plate; however, it remains unclear when this process began to affect the mantle and the related magmatism. Here we present a systematic study on the source lithology of Late Mesozoic basalts in this area to highlight a link between lithological variations of mantle and subduction process of paleo‐Pacific plate. Late Mesozoic basalts can be subdivided into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…All these compositional characteristics apply to the Siling gabbro. Its significant depletions in Nb and Ta is, moreover, a characteristic fingerprint of subduction‐zone magmatism (e.g., Duggen et al, ; Zeng et al, ), and its strong enrichment in Pb relative to Ce, and the resulting positive Pb anomalies and low Ce/Pb ratios (3–6), likely reflects the contribution of pelagic sediment in its source (Plank, ). It is therefore concluded that the mafic magma parent of the Siling gabbro was formed through partial melting of a pyroxenite‐bearing enriched SCLM that was previously modified by Neoproterozoic subduction‐related metasomatism (e.g., Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…All these compositional characteristics apply to the Siling gabbro. Its significant depletions in Nb and Ta is, moreover, a characteristic fingerprint of subduction‐zone magmatism (e.g., Duggen et al, ; Zeng et al, ), and its strong enrichment in Pb relative to Ce, and the resulting positive Pb anomalies and low Ce/Pb ratios (3–6), likely reflects the contribution of pelagic sediment in its source (Plank, ). It is therefore concluded that the mafic magma parent of the Siling gabbro was formed through partial melting of a pyroxenite‐bearing enriched SCLM that was previously modified by Neoproterozoic subduction‐related metasomatism (e.g., Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Cenozoic and Mesozoic intraplate basalts are sporadically scattered in the Cathaysia Block. These basalts are spatially and temporally associated with the subduction of the Paleo-Pacific Plate and have mixed enriched-mantle Ⅱ (EM2) and depleted mantle sources (Ho et al, 2003;Chen et al, 2008;Zeng et al, 2016). However, compared to fresh Cenozoic basalts, most Mesozoic basalts underwent varying degrees of chloritization and epidotization (Meng et al, 2012;Cen et al, 2016), thus providing an opportunity to study the Li isotopic behavior during low-temperature alteration processes.…”
Section: Geological Background and Samplesmentioning
confidence: 99%
“…2. During both the Middle Jurassic (175-170 Ma) and Early Cretaceous (140 Ma,105 Ma,and 90 Ma), strong lithospheric extension took place, which resulted in the emergence of the large number of rift basins, as well the occurrence of extensive magmatism (e.g., the emplacement of mafic dykes and A-type granite, the eruption of basalt, adakite, bimodal volcanic rock, and the development of complex, metamorphic core complexes); large-scale mineralization in extensional setting is also a key product of these activities found across South China (Guo et al, 2001;Deng et al, 2003;Dai et al, 2005;Yan et al, 2005;Dai, 2007;Shen et al, 2008;Wang et al, 2008;Xu et al, 2009;Duan et al, 2011;Li et al, 2012;Qi et al, 2012;Qi et al, 2012Qi et al, , 2016Liu et al, 2012dLiu et al, , 2013Xia et al, 2015;Cen et al, 2016;Zeng et al, 2016;Wang et al, 2005bWang et al, , 2016Pan et al, 2018). Previous studies have shown that subsequent plate convergence during the Indosinian, South China was affected by oblique subduction-dominated tectonics at about 175 Ma, relating to the paleo-Pacific Plate (Deng et al, 2003).…”
Section: Origin Of the Studied Wmgl Mafic Dykesmentioning
confidence: 99%